The Effects of the 2010 Haiti Earthquake on Children's Nutrition and Education - Marina Dodlova; Michelle Escobar Carias; Michael Grimm (Institute of Labor Economics (IZA), 2023)
We assess the impact of the 2010 Haiti earthquake on children's nutrition and education. We combine geo-coded shaking intensity data with four waves of the Haiti Demographic Health Survey, two administered before and two after the earthquake. We find lasting negative impacts of the earthquake on children's stunting and wasting as well as on school enrolment and attendance. A one standard deviation increase in shaking intensity raises infant stunting by 0.08 standard deviations and wasting by 0.04 standard deviations. Our estimates account for the millions in aid funds allocated by the World Bank to overcome the earthquake's aftermath. This aid mitigated but could not fully prevent the adverse effects on children's health and education. The results are robust to alternative specifications and different measures of exposure to the earthquake. Our results highlight the need for aid in poor areas affected by natural disasters to prevent infant malnutrition and poor education. Reduced children's health and education will have lasting private and social costs, which could easily exceed the necessary costs to counter these effects.
Keywords: I15; I25; Q54; O10; 330; natural disasters; earthquake; nutrition; education; school attendance; Haiti